2012
DOI: 10.1016/j.fct.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth, serum biochemistries and n−6 fatty acid metabolism in rats fed diets supplemented with high-gamma-linolenic acid safflower oil or borage oil for 90days

Abstract: Recently, steps have been taken to further developments toward increasing gamma-linolenic acid (GLA) concentration and lowering costs in plant seed oils using transgenic technology. Through identification and expression of a fungal delta-6 desaturase gene in the high linoleic acid safflower plant, the seeds from this genetic transformation produce oil with >40% GLA (high GLA safflower oil (HGSO)). The aim of the study was to compare the effects of feeding HGSO to a generally recognized as safe source of GLA, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
1
12
0
5
Order By: Relevance
“…High level of eicosenoic FA (C20:1) (3.9%) determined by us in BOR confirmed earlier report of Tso, Caldwell, Lee, Boivin, and De Michele (2012), who also found slightly higher share of GLA. Supplementation of diet with Borage oil enhances the levels of n-6 PUFA (dihomogamma-linolenic and arachidonic acid) in the plasma, liver, and vascular tissue of Wistar Kyoto and spontaneously hypertensive rats, and may be responsible for the observed anti-hypertensive effect (Engler & Engler, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…High level of eicosenoic FA (C20:1) (3.9%) determined by us in BOR confirmed earlier report of Tso, Caldwell, Lee, Boivin, and De Michele (2012), who also found slightly higher share of GLA. Supplementation of diet with Borage oil enhances the levels of n-6 PUFA (dihomogamma-linolenic and arachidonic acid) in the plasma, liver, and vascular tissue of Wistar Kyoto and spontaneously hypertensive rats, and may be responsible for the observed anti-hypertensive effect (Engler & Engler, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…The final BW of animals in all groups was similar. Therefore, the results are consistent with previously reported outcomes, where the growth characteristics and FI remained unchanged during the 4‐week period of feeding with either soybean oil, coconut oil, or evening primrose oil …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results are consistent with previously reported outcomes, where the growth characteristics and FI remained unchanged during the 4-week period of feeding with either soybean oil, 46,47 coconut oil, [48][49][50][51] or evening primrose oil. 52,53 The cornerstone of current dietary advice is the recommendation to reduce the intake of saturated FAs and replace it with PUFAs, as a means of decreasing the risk of CVD. 54 However, several meta-analyses of observational studies have consistently indicated that the intake of saturated FAs is independently associated with cardiac function, and that current evidence does not clearly support the CV guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…GLA also inhibits tumour growth, exerts good anti‐inflammatory activity and provides immunity in the early stages of sepsis . Therefore, applying GLA to functional food, dietary supplements and personal care products substantially promotes the recognition of the nutritional and health benefits of PUFAs . However, borage oil is vulnerable to oxidation because of its high omega‐6 PUFA content, and the consequent production of undesirable flavours affects the sensory properties of borage‐oil‐containing foods.…”
Section: Introductionmentioning
confidence: 99%